Diffusion of the human security approach in Costa Rica: between the acceptance and resistance of the epistemic communities - Colmenares Zapata, Alexis (2019)
Policy diffusion studies seldom explain the role that epistemic communities can play as promoters or blockers in the propagation of an idea or policy. The objective of this article is to analyze the role of the Costa Rican epistemic community of human rights in the diffusion of the human security approach. The study suggests that human rights community have played an ambiguous role in spreading the human security approach in Costa Rica, which ranks between acceptance and rejection. In addition, this research finds that the mechanisms of coercion, competition, and socialization may have an influence on actors other than the State or government, such as international organizations.